2011
DOI: 10.1590/s1516-89132011000300021
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional requirements of Zymomonas mobilis CCT 4494 for levan production

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, generalizations should be avoided for the fermentation conditions due to the diversity of the nutritional and environmental requirements of the EPS producer strains (23). Optimum conditions for EPS synthesis are affected by limitations of nitrogen and phosphate sources, oxygen content, pH, temperature, proportion between the air and medium volume, agitation rate, inoculum size and also nutrients in the culture medium (24). Therefore, in this study, effective stimulating factors for microbial levan production by H. smyrnensis AAD6 T were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…However, generalizations should be avoided for the fermentation conditions due to the diversity of the nutritional and environmental requirements of the EPS producer strains (23). Optimum conditions for EPS synthesis are affected by limitations of nitrogen and phosphate sources, oxygen content, pH, temperature, proportion between the air and medium volume, agitation rate, inoculum size and also nutrients in the culture medium (24). Therefore, in this study, effective stimulating factors for microbial levan production by H. smyrnensis AAD6 T were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Levan concentration is influenced mainly by sucrose concentration, and also by other factors such as incubation time, temperature, initial pH, presence of yeast extract and Mg 2+ , NaCl, thiamine content, etc. ( Ernandes and Garcia-Cruz, 2011 ; Santos et al, 2014 ; Silbir et al, 2014 ; Zhang et al, 2014 ; Santos-Moriano et al, 2015 ; Sarilmiser et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Ernandes and García‐Cruz () with free cells showed that increasing the sucrose concentration proportionately affects cell growth and levan formation. However, this was not observed in the present study.…”
Section: Resultsmentioning
confidence: 99%